Analysis Of Nurse Performance Using The Balance Scorecard Method At South Nias Hospital - O'ozisokhi Telaumbanua; Irza Haicha Pratama; Ermi Girsang (International Journal of Health and Pharmaceutical (IJHP), 2024)
Performance measurement is needed to assess the accountability of an organization in producing better and right on target services and performance. The Balanced Score Card was created to overcome a problem in the organization regarding weaknesses in an executive performance measurement system. The purpose of this study was to analyze the performance of nurses using the balanced scorecard method at South Nias Hospital. This type of research is descriptive analytic with a quantitative approach with a crosssectional design. The sampling technique in this study was Arikunto's formula, based on this formula, the number of samples in this study became 31 people. The results of the study explain that there is a relationship between financial, consumer, innovative and perspective with the performance of nurses in South Nias Hospital. This research can be used as basic information and data for improving the quality of services at South Nias Hospital.